On the mechanics of software development with Microsoft Access for ERP in maintenance - Htayy Win. (2008)
ERP (Enterprise Resource Planning) is a must-have program for every company because it handles all the business processes/functions (marketing and sales, production and materials management, accounting and finance, human resources) in a single streamlined integrated database environment. But ERP system implementation is a very costly and time-consuming task.